Phase III Randomized Trial of Dose Intensive Neoadjuvant Chemotherapy with or Without G-CSF in Locally Advanced Breast Cancer: Long-Term Results - Arun, Banu K. (AlphaMed Press, 2011)
OBJECTIVE. To compare the pathologic complete response (pCR) rate of patients treated with 5-fluorouracil (5-FU), doxorubicin, and cyclophosphamide (FAC) versus dose-intense FAC plus G-CSF in the neoadjuvant setting and to compare the delivered dose intensity, disease-free survival (DFS) and overall survival (OS) times, and toxicity between treatment arms in patients with breast cancer. METHODS. Patients were randomized to receive preoperative FAC (5-FU, 500 mg/m(2); doxorubicin, 50 mg/m(2); cyclophosphamide, 500 mg/m(2)) every 21 days for four cycles or dose-intense FAC (5-FU, 600 mg/m(2); doxorubicin, 60 mg/m(2); cyclophosphamide, 1,000 mg/m(2)) plus G-CSF every 18 days for four cycles. RESULTS. Two hundred two patients were randomly assigned. The median follow-up was 7.5 years. Patients randomized to FAC plus G-CSF had a higher pCR rate as well as clinical complete response rate; however, these differences were not statistically different from those with the FAC arm. Patients in the FAC + G-CSF arm had a higher delivered dose intensity of doxorubicin in the neoadjuvant and adjuvant settings than those in the standard FAC arm. DFS and OS times were not significantly different between the two groups. However, the OS and DFS rates were significantly higher for patients who achieved a pCR than for those who did not. Thrombocytopenia, febrile neutropenia, and infection rates were higher in the FAC + G-CSF arm. CONCLUSIONS. A higher delivered dose intensity of doxorubicin with the FAC + G-CSF regimen did not result in a statistically significant higher pCR rate. However, patients who achieved a pCR experienced longer DFS and OS times.